Redrawing the maps in Kashmir: New geopolitical realities in the conflict between China, India, and Pakistan - Christian Wagner; Angela Stanzel (Stiftung Wissenschaft und Politik (SWP), 2020)
The political geography of Kashmir has changed radically in recent months. The starting point was the Indian government's decision on 5 August 2019 to divide the state of Jammu and Kashmir (J&K) into two Union territories. In response, Islamabad published a map on 4 August 2020 showing all of Kashmir as part of Pakistan. At the end of September 2020, the Chinese government terminated the status quo with India in the Ladakh/Aksai Chin region. This indicates a new phase in the conflict over Kashmir, in which China and Pakistan could work more closely together. In addition, the conflict is being expanded to include a new geopolitical dimension because, for China, the dispute with India is now also part of the struggle with the United States over the future distribution of power in the Indo-Pacific.
Keywords: 320